EFEKTIVITAS PANITIA PEMUTAHIRAN DATA PEMILIH (PPDP) PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR DI KOTA KOTAMOBAGU TAHUN 2015 - Machmud, Rachmat (HOLISTIK, Journal Of Social and Culture, 2019)
Political participation is at the heart of democracy, the democratic absence of a political system is determined by whether or not the low level of political participation of its citizens. Regarding DPT problem, on 6 July 2009 the Constitutional Court made the decision No. 102/PUU-VII/2009 which specifies that citizens who are not registered in the list of voters may exercise suffrage using the identity of residence such as resident ID card, family Card (KK), and passport. This decision is also contained in article 40 paragraph 5 of Law No. 8 of 2012 on the elections of DPR (House of Representatives), DPD (Regional Representative Council) and the DPRD (regional people's Representative Council) that the community chooses by using the KTP, And the passport will be included in the Special selector list (DPK).The election implementation in this case KPU even though it has been a lot of efforts to repair but must be recognized until now still found various problems in this case list of voters.Achievement of objectives in order to update the data that has been done results from the data update of the selector is not maximized because there is still a report of the community to the election supervisor because, PPDP goes without any supervision Time span of a scheduled month.Keywords: political, participation, democracy